Quality assessment, antimicrobial activity organic sunflower honey and use of Maldi-tof mass spectrometry for the identification bacteria isolated from honey - Milosavljević, Saša; Zugic Petrovic, Tanja; Mladenović, Katarina; Grujović, Mirjana; Kolašinac, Stefan; Orović, Dragan (Progress in Nutrition, 2021)
The aim of this study was to investigate the physicochemical parameters of quality, microbiological safety and antimicrobial potential of four samples of organic sunflower honey from the Banat area (northeastern Serbia). Humidity, ash, pH, free acidity, electrical conductivity, hydroxymethylfurfural content, sugar content and diastase activity were measured. Microbiological analysis revealed the presence of total aerobic mesophilic bacteria, coliforms, aerobic endospores, lactic acid bacteria (LAB) and a good number of molds and yeasts. The isolate identification was carried out using Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). The antimicrobial effect of organic sunflower honey was investigated on five ATCC strains of bacteria: Staphilococcusaureus ATCC 29213; Escherichia coli ATCC 25922; Salmonella enterica ATCC 10708; Yersinia enterocolitica ATCC 23715; and Bacillus subtilis ATCC 23857. The results of the study showed that all honey samples meet international quality standards for all physicochemical parameters. Microbiological analysis of Sunflower honey confirmed the total bacterial counts for all samples ranged from1.80 to 1.85 x10-2cfu/g-1, whereby no presence Clostridium spp., coliform bacteria, as well as molds was detected. Investigation of the antimicrobial activity of honey samples revealed that all bacteria showed clear zones of inhibition in honey concentrations of 40-100%, which is a satisfactory result for flower honey.